(untitled) (Biological Sciences - PJSIR, 2022)
by hydration to saturation, immediately after removal from incubation at 25°, by soaking in water for 2 hrs. The excess water was removed by filtration and the hydrated straw, after weighing, was allowed to dehydrate at 25° for 24,48 and 72 hrs and the dehydrated straw weighed again.